Development of a smartphone-based colorimetric detection for quantification of vitamin C in dietary supplements and skin care products: https://doi.org/10.69692/SUJMRD0802206 - Syhalath, Chanthakhy; Phomkeona, Kesiny; Chounlamany, Vanseng; Yamaguchi, Tsuyoshi; Phouthavong, Vanpaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research project presents a development of an assay tool for quantification of vitamin C in dietary supplements and skin care products. The proposed method was developed based on decolorization of acidic potassium permanganate (KMnO4) by vitamin C through a redox reaction, with subsequent colorimetric detection by using digital imaging. The imaging was carried out using smartphone camera and free-downloaded RGB color detector application. To obtain optimal conditions, influential parameters such as light source position installed inside a 19 cm × 46 cm × 10 cm lightbox, reagent concentrations, and reaction time were studied. To the best conditions, good linearity (r2 > 0.99) in the range 1–70 mg vitamin C/L was obtained. Relative standard deviation was less than 3.9% indicating high precision. The proposed method was validated by quantification of vitamin C content in 15 sample solutions using the proposed method in comparison with the reference iodometric titration method. The results obtained from those two methods were not significantly different using paired t-test at confidence level of 95% (texp=0.41, tcrit=2.14). The results indicated that utilizing smartphone camera with free-downloaded color detector application is possible as an alternative analysis tool for determination of vitamin C.